Analisis beban kerja pada pekerja Assembly Lavatory di PT INKA Multi Solusi dengan metode Workload Analysis (WLA) - Primadhiya, Fairuzzayyan; Rochmoeljati, Rr (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Lavatories are among the top items produced by INKA Multi Solusi, a manufacturing company that makes railway components. So the workload of workers needs to be considered, especially the assembly section because it rarely uses machine assistance with quite high demand. The time study approach was used to establish working hours, and workload analysis was used to determine the ideal workforce size. Three overload activities and two underload activities are identified based on the workload calculation. Meanwhile, the workload analysis results must be applied throughout the company to apply the ideal amount of workers., namely 2 people for installing partitions, 1 person for installing maulding, 2 people for piping, 2 people for installing closet sets, and 2 people for installing doors. Additionally, INKA Multi Solusi has established the right total number of employees based on the research.